Screening for cervical cancer: is there a place for incorporating tests for the human papillomavirus? - Beral, V; Day, N (1992)
Well organized screening programmes for cervical cancer, based on exfoliative cervical cytology, are known to be effective at reducing the incidence of invasive cervical cancer and mortality from the disease. HPV testing should not replace cervical cytology as the first-line approach in screening for cervical cancer, as HPV testing is not sufficiently reliable and some cancers are not associated with HPV infection. Even though there are many unanswered questions about the validity of HPV tests, it is timely to consider whether HPV testing might improve the management of the substantial number of women whose smears are neither clearly normal nor abnormal, but are described as atypical, suspicious or mildly dyskaryotic. The efficacy and costs of incorporating HPV testing into a cervical cancer screening programme need to be evaluated in controlled trials.